Cath’s Anxiety in Rainbow Rowell’s Fangirl - Musdalifa Rumatiga; Tri Pramesti (Austronesian: Journal of Language Science & Literature, 2023)
This research delves into the anxiety experience of Cath, the central protagonist in Rainbow Rowell’s novel “Fangirl.” The study addresses to investigate three key issues: the symptoms of Cath’s anxiety, its underlying causes, and its effects. Drawing from Sigmund Freud’s literary psychology theory, this qualitative research aims to explore Cath’s anxiety journey. The primary source of information is the novel “Fangirl” itself. Employing techniques such as textual analysis, note-taking, keyword identification, and data collection. This study presents a comprehensive analysis of Cath’s psychological landscape. The research reveals that Cath encounters two prominent anxiety symptoms. Firstly, she experiences panic disorder upon her initial move to the hostel, where she encounters a male student in what should be an exclusively female dormitory. Secondly, stress disorder emerges as a result of her twin sister’s renewed connection with their mother, prompting Cath to confront her past. Cath’s anxiety roots itself in familial circumstances, encompassing her parents’ divorce, her father’s illness, and the strained relationship with her twin sister, Wren. This familial dynamic contributes to Cath’s dependency and introverted tendencies. The implications of Cath’s anxiety are far-reaching. The negative impact of her anxiety is manifested in her reliance on her twin sister, hindering her personal growth and self-reliance. By applying Sigmund Freud’s literary psychology theory, the research provides insights into the symptoms, causes, and effects of Cath’s anxiety. This analysis underscores the significance of understanding literary characters’ psychological experiences and their broader implications for personal growth and relationships.